Dyeing efficiency of Lawsonia inermis (Henna) and ferrous sulphate on silk fibre (Indian Journal of Fibre & Textile Research (IJFTR), 2025)
s study evaluates the dyeing efficiency of Lawsonia inermis (Henna) at varying concentrations on silk fibres using 3% ferrous sulfate as a mordant. Preliminary trials suggest 3% of ferrous sulphate as the optimal mordant concentration, while henna dye percentages of 10%, 15% and 20% are assessed. The dyed samples are analyzed for absorbance, colour coordinates, colour strength and fastness properties. Results indicate that 15% henna dye, along with 3% ferrous sulphate, achieves better dyeing performance on silk fibres.